The Relationship between Family Knowledge and Family Compliance Behavior in Assistance Rules in the Ponek Room of RSUD dr. Abdul Rivai - Meiske Paimbong; Hestri Norhapifah; Widya Astutik; Ridha Wahyuni (Institute of Computer Science (IOCS), 2022)
PONEK services are an effort to support the accelerated reduction of MMR and AKN through the provision of integrated services for mothers and newborns. The success of PONEK requires reliable management in the form of family rules that accompany patients in the hospital. Preliminary study of RSUD dr. Abdul Rivai still has a companion family who violates the rules regarding discipline in the PONEK Room. Objective: Knowing the relationship between family knowledge and family compliance behavior with the mentoring rules. Methods: This type of analytic survey research is cross sectional design. The population is the accompanying family of patients at Ponek RSUD dr. Abdul Rivai numbered 250 people, with a sample of 154 people. Data analysis using chi-square. Result: Most family knowledge about mentoring rules is good (55, 8%) and the behavior of family obedience to the mentoring rules is the most obedient (63.6%). There is a relationship between the level of family knowledge and the behavior of family compliance with the mentoring rules (p value: 0.000). Conclusion: knowledge is a factor related to family obedience behavior in mentoring rules.